Evaluation of a Single-Dose Nucleoside-Modified Messenger RNA Vaccine Encoding Hendra Virus-Soluble Glycoprotein Against Lethal Nipah virus Challenge in Syrian Hamsters. (21st November 2019) - Lo, Michael K; Spengler, Jessica R; Welch, Stephen R; Harmon, Jessica R; Coleman-McCray, JoAnn D; Scholte, Florine E M; Shrivastava-Ranjan, Punya; Montgomery, Joel M; Nichol, Stuart T; Weissman, Drew; Spiropoulou, Christina F
Abstract: In the absence of approved vaccines and therapeutics for use in humans, Nipah virus (NiV) continues to cause fatal outbreaks of encephalitis and respiratory disease in Bangladesh and India on a near-annual basis. We determined that a single dose of a lipid nanoparticle nucleoside-modified messenger RNA vaccine encoding the soluble Hendra virus glycoprotein protected up to 70% of Syrian hamsters from lethal NiV challenge, despite animals having suboptimally primed immune responses before challenge. These data provide a foundation from which to optimize future messenger RNA vaccination studies against NiV and other highly pathogenic viruses.